PENGARUH MODEL CONCEPT SENTENCE TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI DI SEKOLAH DASAR - Lestari, Gita Dwi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The research problem of this research is there any effect of applying concept sentence model to the students writing skill in narrative text on the fifth grade students of SDN 36 Pontianak Kota. The purpose of this researchÂ is to describe the effect of concept sentence model to the students writing skill in narrative text on the fifth grade students. This research usedÂ experiment method with quasi experiment design form of non equivalent control group design. The population is all of the students of two classes with 49 students in total, the sample used is simple random sampling. Technique of data collecting is direct observation technique and measuring, tools of data collecting is written test. Based on data analysis, the mean score of post test in experiment class is 75,17, and the mean score of post test in control class is 64,24. This showed the significant difference of mean score of writing skill in narrative text on the fifth grade students between experimental class and control class. After done the t-test with dk 47 on 5% significant level as know as table t=2,01 obtained count (table t =2,01). It showed that Ha is accepted. It means that concept sentence model gave the significant effect to the students writing skill in narrative text. Based on the result of effect size it has, been goten ES is 1,00 which is meant it is (high criteria). Based on that result, can be concluded that learning by using concept sentence model gave the high (effect) to the students writing skill in narrative text. Keyword : Influence, Concept Sentence Model, Writing Skill in Narrative